The Impact of Social Dynamics on the Management of Islamic Political Organizations in the Modern Era - Wulandari, Irma (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
In the modern era, Islamic political organizations face significant challenges arising from evolving social dynamics, globalization, and advances in information technology. Rapid social changes, particularly in technology and communication, necessitate that Islamic political organizations adjust their structures, strategies, and management methods to remain relevant and to appeal to younger generations who are increasingly engaged in political and social issues. This study aims to analyze the impact of social changes on the management of Islamic political organizations, including the adaptations made in response to growing demands for public participation, transparency, and the pressures of globalization to maintain a positive image. The research employs a qualitative, literature-based approach, drawing on secondary data sources, including national survey reports, organizational reports, and case studies of various Islamic political organizations in Indonesia, Malaysia, and Turkey. Data analysis is conducted descriptively to depict the adaptations made by these organizations in addressing the challenges of modernity. The findings indicate that developments in information technology, particularly through social media, have prompted Islamic political organizations to adopt more flexible management structures, increase youth engagement, and expand their outreach campaigns. This increase in youth participation has been accompanied by greater demands for transparency and accountability, driving Islamic political organizations to adopt more open management principles. Additionally, globalization has heightened the need for these organizations to maintain their Islamic identity while aligning their values with global norms and demands. This research provides valuable insights for Islamic political organizations on the adaptive strategies necessary to retain public relevance and support in the modern era, while upholding their core values.